Maternal protein restriction changes structural and metabolic gene expression in the skeletal muscle of aging offspring rats - Valente, Jéssica Silvino [UNESP] (2021)
Maternal protein restriction affects postnatal skeletal muscle physiology with impacts that last through senility. To investigate the morphological and molecular characteristics of skeletal muscle in aging rats subjected to maternal protein restriction, we used aged male rats (540 days old) born of dams fed a protein restricted diet (6% protein) during pregnancy and lactation. Using morphological, immunohistochemical and molecular analyses, we evaluated the soleus (SOL) and extensor digitorum longus (EDL) muscles, muscle fiber cross-sectional area (CSA) (n=8), muscle fiber frequency (n=5) and the gene expression (n=8) of the oxidative markers (succinate dehydrogenase-Sdha and citrate synthase-CS) and the glycolytic marker (lactate dehydrogenase-Ldha). Global transcriptome analysis (n=3) was also performed to identify differentially regulated genes, followed by gene expression validation (n=8). The oxidative SOL muscle displayed a decrease in muscle fiber CSA (*p<0.05) and in the expression of oxidative metabolism marker Sdha (***p<0.001), upregulation of the anabolic Igf-1 (**p<0.01), structural Chad (**p<0.01), and Fmod (*p<0.05) genes, and downregulation of the Hspb7 (**p<0.01) gene. The glycolytic EDL muscle exhibited decreased IIA (*p<0.05) and increased IIB (*p<0.05) fiber frequency, and no changes in muscle fiber CSA or in the expression of oxidative metabolism genes. In contrast, the gene expression of Chad (**p<0.01) was upregulated and the Myog (**p<0.01) gene was downregulated. Collectively, our morphological, immunohistochemical and molecular analyses showed that maternal protein restriction induced changes in the expression of metabolic, anabolic, myogenic, and structural genes, mainly in the oxidative SOL muscle, in aged offspring rats.